Konstruksi Hukum Operasi Tangkap Tangan (OTT) dalam Perkara Korupsi: Perspektif Hak Asasi Manusia - Mhd Hasbi; Muhammad Dhobit Azhary Lubis; Surya Hamdani; Annisa Danti Avrilia Ningrum (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
This article analyzes the legal construction of Hand-Catching Operations (OTT) conducted by the Corruption Eradication Commission in Indonesia's criminal justice system, which faces a fundamental dilemma between law enforcement effectiveness and human rights protection. The practice of OTT, despite its significant success rate, often raises controversies regarding potential violations of suspects' constitutional rights. The problem becomes increasingly complex when OTT is conducted without an explicit and definitive legal framework in statutory regulations, thus opening wide interpretive spaces and potentially causing arbitrariness in law enforcement. The purpose of this article is to examine the existing legal construction of OTT in Indonesian legislation and its implications for suspects' human rights protection, to analyze how international human rights standards should be integrated into OTT mechanisms, and to formulate an ideal legal construction that accommodates substantive justice principles without sacrificing law enforcement effectiveness. This research employs normative legal research methods based on norm ambiguity, using statutory approach, conceptual approach, and analytical approach. Document study techniques are utilized for legal material exploration, with qualitative analysis applied to examine the meaning of legal norms systematically and teleologically. The research findings demonstrate that current legal construction of OTT suffers from significant normative gaps lacking explicit regulation of definitions, requirements, procedures, and limitations. This study offers an ideal legal construction formulation that integrates human rights perspectives through comprehensive regulation encompassing strict procedural requirements, independent oversight mechanisms, constitutional rights guarantees, publication limitations, mandatory audio-visual documentation, strict sanctions for procedural violations, and compensation-rehabilitation mechanisms for wrongful arrest victims, thereby creating a just corruption criminal justice system respecting human dignity.